The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/jnc.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Community and Provider Perspectives on Molecular HIV Surveillance and Cluster Detection and Response for HIV Prevention: Qualitative Findings From King County, Washington

Abstract: Responding quickly to HIV outbreaks is one of four pillars of the U.S. Ending the HIV Epidemic (EHE) initiative. Inclusion of cluster detection and response in the fourth pillar of EHE has led to public discussion concerning bioethical implications of cluster detection and response and molecular HIV surveillance (MHS) among public health authorities, researchers, and community members. This study reports on findings from a qualitative analysis of interviews with community members and providers regarding their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Further complicating these efforts is the conflation between concerns about HIV-ME and concerns about HIV surveillance generally. 20…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating these efforts is the conflation between concerns about HIV-ME and concerns about HIV surveillance generally. 20…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception, MHS has been fraught with objections and ethical concerns from community members due to a lack of transparency and consent to use phylogenetic data for CDR; its potential for use in establishing the directionality of transmission; and possible criminalization, the potential loss of privacy, and the perpetuation of stigma in already marginalized communities [ 17 , 28 ]. Researchers indicated that community and provider concerns remained despite taking a transparent and proactive approach involving the dissemination of MHS-related information to the Ryan White Planning Council, sharing information on its website, and alerting community members to clusters with multidrug-resistant HIV [ 17 ]. Our research findings for Theme 5 demonstrate that these concerns also impact public health professionals carrying out CDR, with this being a prominent concern expressed by our research participants.…”
Section: Discussionmentioning
confidence: 99%
“…Our research findings for Theme 5 demonstrate that these concerns also impact public health professionals carrying out CDR, with this being a prominent concern expressed by our research participants. Community engagement around MHS-related activities has largely been left to individual health departments, but a centralized approach to disseminating MHS-related information and promoting equitable community engagement to all stakeholders may be beneficial, including those within the field of public health [ 17 ]. Approaches that center on meaningful community involvement will be crucial to alleviating these concerns and thus improving the success of CDR [ 17 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations